Digital sound & music concepts, applications, and science - Burg, Jennifer; Romney, Jason; Schwartz, Eric (Franklin, Beedle & Associates, Inc., 2016)
"This book presents material that explains the science and mathematics of digital sound in a way that connects it to theatre, movies, and music production"...